2019
DOI: 10.1186/s12875-019-0975-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ health literacy in relation to the preference for a general practitioner as the source of health information

Abstract: Background For many patients, the general practitioner (GP) is the most important point of contact for obtaining information about a wide range of health topics. However, patients with different characteristics may seek health information from different sources, such as friends or the internet. The relationship between patient characteristics and preferences for information sources is understudied. We investigate which information sources are used by patients for health-related questions and how t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…Angesichts der breiten Verfügbarkeit und leichten Zugänglichkeit gesundheitsrelevanter Informationen im Internet überrascht, dass nur etwa ein Fünftel der Befragten bei akutem Informationsbedarf zuerst online nach Informationen sucht. Derartige Tendenzen zeigen sich allerdings auch in anderen Studien [8,32,33]. Der eher seltene Zugriff auf das Internet als primäre Quelle korrespondiert mit dem geringeren Vertrauen, das die Befragten in das Internet als Quelle für Gesundheitsinformationen legen, was auch aus anderen Studien bekannt ist [31,34] nem Arztbesuch [31].…”
Section: Zusammenfassung Und Diskussionunclassified
“…Angesichts der breiten Verfügbarkeit und leichten Zugänglichkeit gesundheitsrelevanter Informationen im Internet überrascht, dass nur etwa ein Fünftel der Befragten bei akutem Informationsbedarf zuerst online nach Informationen sucht. Derartige Tendenzen zeigen sich allerdings auch in anderen Studien [8,32,33]. Der eher seltene Zugriff auf das Internet als primäre Quelle korrespondiert mit dem geringeren Vertrauen, das die Befragten in das Internet als Quelle für Gesundheitsinformationen legen, was auch aus anderen Studien bekannt ist [31,34] nem Arztbesuch [31].…”
Section: Zusammenfassung Und Diskussionunclassified
“…Literature indicates that the Internet has become increasingly important as a source of information for child health [1]. Moreover, the number of online portals developed to meet the needs of parents has greatly increased, offering information on a wide variety of topics such as deliveries, breast-feeding, and children's diseases [2]. O'Connor and Madge [3] argue that the shift to the Internet is due to parent's appreciation of its 24-h availability.…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that the Internet has become increasingly important as a source of information for child health [1]. Moreover, the number of online portals developed to meet the needs of parents has greatly increased, offering information on a wide variety of topics such as deliveries, breast-feeding, and children's diseases [2]. O'Connor and Madge [3] argue that the shift to the Internet is due to parent's appreciation of its 24-hour availability.…”
Section: Introductionmentioning
confidence: 99%
“…[20] shows that parents whose children suffer from high fever seek advice from doctors, books or other parents, but less often from the Internet, while Yardi et al found parents of a child with a disability to access the internet more frequently than parents of healthy children [21]. A representative study among adults in Germany has shown that those with multiple chronic conditions preferred a general practitioner as an information source compared with those without chronic conditions [2]. Parents with a disabled child may thus experience a particular need for specific health information.…”
Section: Introductionmentioning
confidence: 99%